AKTIVISME MAHASISWA DAN KESEHATAN MENTAL: SOSIOLOGI KESEHATAN DI DALAM ORGANISASI INTRA-KAMPUS - Amelia, Ni Putu Dila; Ranteallo, Ikma Citra; Tamim, Imron Hadi (JURNAL ILMIAH SOSIOLOGI: SOROT, 2025)
Student activism is an integral part of campus life that offers benefits but also has consequences for mental health. This study aims to analyze the relationship between student organizational activities and their impact on the mental health of students at Udayana University. Using a qualitative approach and in-depth interviews, this research explores the experiences of students actively involved in intra-campus organizations and the factors influencing their psychological well-being. The findings reveal that organizational involvement fosters social and leadership skills but also increases stress, anxiety, and mental fatigue due to academic pressure and organizational responsibilities. Michel Foucault's theories of Biopower and Biopolitics are applied to understand how organizational structures and social expectations shape students' experiences in activism. This study provides insights into the importance of balancing organizational activities and students' mental health, along with recommendations for campus policies that better support student well-being..   Keyword: biopolitics,  biopower, campus organization, mental health, studenta activism